2022
DOI: 10.1002/uog.23761
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of supratentorial anomalies assessed by magnetic resonance imaging in fetuses with open spina bifida

Abstract: What are the novel findings of this work?This study demonstrates that half of fetuses eligible for prenatal open spina bifida repair have structural brain anomalies, such as an abnormal corpus callosum or heterotopia. Such anomalies were more likely in the presence of a lumbar or higher lesion and wider lateral ventricles (≥ 15 mm). What are the clinical implications of this work?Our findings highlight the relevance of detailed prenatal and preoperative assessment of the brain in fetuses with open spina bifida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…US scans were performed using transabdominal convex (3)(4)(5) probes. Some cases were detected accidently by routine US examination, which included biometric parameter measurements.…”
Section: Ultrasound Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…US scans were performed using transabdominal convex (3)(4)(5) probes. Some cases were detected accidently by routine US examination, which included biometric parameter measurements.…”
Section: Ultrasound Scanningmentioning
confidence: 99%
“…Foetal neurosonography is the modality of choice for central nervous system (CNS) malformations given that it is noninvasive, widely available, cheap and safe for both the mother and foetus [1,2]. The major disadvantages of US include tiny intracranial abnormal ndings shielding by calvaria, maternal obesity and foetal irregular head position [3]. It was reported that prenatal US yielded a sensitivity and speci city of 72.2% and 100% for diagnosis of fetal CNS abnormalities, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we described the nature and occurrence of supratentorial abnormalities in fetuses with spina bifida [ 16 ]. Proper assessment is important for counselling women about fetal surgery [ 17 ].…”
Section: Fetal Brain Mri In Spina Bifida Apertamentioning
confidence: 99%
“…Besides ventriculomegaly, evidence of damage to white matter tracts and abnormalities of the corpus callosum [ 18 ] or indications of abnormal neuronal migration are frequently observed in fetuses with open spina bifida [ 14 15 19 20 21 22 ]. When using MRI in fetuses meeting the criteria for fetal surgery on ultrasound findings, half of them were found to have corpus callosum abnormalities and/or ventricular wall abnormalities [ 16 ]. This number is in line with findings in a recent systematic review by our group [ 23 ].…”
Section: Fetal Brain Mri In Spina Bifida Apertamentioning
confidence: 99%
See 1 more Smart Citation